1988
DOI: 10.3758/bf03210415
|View full text |Cite
|
Sign up to set email alerts
|

Masking the motions of human gait

Abstract: In three experiments we tried to mask the motions of human gait. We represented human walkers as a set of 11 computer-generated elements on a display monitor, moving as a nested hierarchy of motions that mimicked the motions of the head and major joints. The walker was seen in sagittal view, facing either right or left.and walking as if on a treadmill. On the walker was superimposed a simultaneous mask composed of elements with the same brightness, shape, and subtense as those of the walker. We varied the mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
129
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(139 citation statements)
references
References 35 publications
6
129
0
4
Order By: Relevance
“…The extraordinary ability of humans to perceive biological motion has been well established since Johansson's [18] experiments in which human actors with point-lights attached to major joints were recorded and later viewed as images showing only a few moving dots. Viewers easily identified the human figures and their activities, such as walking, even in the presence of substantial "masking" by other dots [11]. Even hidden characteristics of motion such as the weight of a box [32] or distance of a thrown object [20] were discernible to viewers of these point-light displays.…”
Section: Intelligibility Of Swarm Behaviormentioning
confidence: 98%
“…The extraordinary ability of humans to perceive biological motion has been well established since Johansson's [18] experiments in which human actors with point-lights attached to major joints were recorded and later viewed as images showing only a few moving dots. Viewers easily identified the human figures and their activities, such as walking, even in the presence of substantial "masking" by other dots [11]. Even hidden characteristics of motion such as the weight of a box [32] or distance of a thrown object [20] were discernible to viewers of these point-light displays.…”
Section: Intelligibility Of Swarm Behaviormentioning
confidence: 98%
“…The authors provide additional evidence in support of effector-independent mechanisms for agency in a second study, by combining the gait agency paradigm with two classical effects from the literature that investigates 1) the processing of upright bodies (inversion) and 2) of the visuo-spatial perspective (direction). Previous research on the perception of body postures (Reed et al, 2003) and biological motion (Cutting et al, 1988), as well as body-part agency , has observed a significant decrease in the performance of perceptual tasks for inverted stimuli (body postures or biological motion), the so-called inversion effect (1). Similarly, agency judgements and other performances decreased for stimuli rendered from a non-egocentred visuo-spatial perspective (David et al, 2006;Vogeley and Fink, 2003), e.g.…”
mentioning
confidence: 99%
“…For instance, scrambling the positions of the moving point lights quite drastically disrupts the perception of recognizable form (Cutting, 1981). Studies in which the point-light walker was masked by scrambled point-light walker elements have shown that detection or direction discrimination is reduced but still possible when local analysis of the stimulus is rendered ambiguous by the duplicated motions (Bertenthal & Pinto, 1994;Cutting, Moore, & Morrison, 1988;Pinto & Shiffrar, 1999). Also, the global percept of form in biological motion can overrule stereoscopic-defined (Bülthoff, Bülthoff, & Sinha, 1998) or motion-defined (Sinha & Poggio, 1996) depth cues.…”
mentioning
confidence: 99%